The Seven Steps of Case Study Development: A Strategic Qualitative Research Methodology in Female Leadership Field - Wanida PHONDEJ; Akkapong KITTISARN; Philip A. NECK (Revista de Management Comparat International)
This study examines the theme of female leadership as a complex concept and an embedded phenomenon. It is in a feminist paradigm that attempts to give voice to women, and works to correct the imbalance generally posited from a predominantly male oriented perspective. In this instance, a case study approach is considered entirely appropriate since it dealt with a process of complex real-life activities in considerable depth. This paper aims to establish the case study approach as a strategic qualitative research methodology in the female leadership field. It discusses the seven steps employed in a case study approach, namely: (1) Justification for the research paradigm and research methodology, (2) Justification for the case study method, (3) Criteria for judging the quality of case study design (4) Designing the case study, (5) Criteria for selecting a case design, (6) Data collection, (7) Case study analysis. While this article reviews the case study approach used to investigate female leadership in Thailand, it undoubtedly will also have application elsewhere.